Determination of the harshness-softness attribute of shadows - Aydin-Yagmur, S.; Dokuzer-Ozturk, L. (SAGE PUBLICATIONS LTD, 2015)
A shadow has two different attributes, harshness-softness and lightness-darkness.A three-phase study designed to quantify these shadow characteristics has been carried out. In the first phase, numerous computer-generated examples of shadows were produced and their harshness-softness attribute was evaluated. The harshness-softness of shadows was graded based on the visual evaluation performed in this phase. In the second phase, the lightness-darkness attribute was graded depending on a calculation-based approach. In the third phase, a mock-up room office was constructed and various lighting scenarios created. The shadows produced under the different lighting scenarios were quantified using the results of the first and second phases. These quantities were then compared with people's judgements of the shadows on the work table. The general impressions of the subjects concerning the shadows on the work table as well as the appearance of faces were also collected. The grading of the shadows in the room based on the results of the first and second phases was found to be consistent with the subjects' evaluations.
Keywords: QUALITY CRITERIUM; Construction & Building Technology; Optics